Social Work with Families and Work-Family Conflict - Oscar Segovia, Amparo; Segado Sánchez-Cabezudo, Sagrario; López Peláez, Antonio (Cuadernos de Trabajo Social, 2013)
The article analyses the direct and modulating effects of family support on burnout in the work-family conflict in Spanish middle-class families. The analysis has been separated by gender in order to better examine differences. Direct relationships in the data show that family support is negatively related to the two subscales of burnout, especially in women. Regarding the buffer effect on work-family conflict, gender differences were found: in men, as expected, support reduced the perception of lack of self-efficacy, however, in women, when the conflict was due to stress or tension, the support had positive effects. If the conflict was due to time, a reverse effect could be found and support was negative. These results confirm the importance of addressing a conflict that is emerging as a major stressor and increasingly prevalent in the field of social services to families. It is a stressor that has increased its presence as a result of the current economic crisis.